Report on industrial attachment with Agilis Communication Technologies Pte Ltd - Chng, Lina. (2008)
The project involves building an SNMP agent into the existing Agilis VSAT products to allow customers to manage the product via Internet. Other protocols such as Telnet and Serial Communication Interface (SCI) are also implemented in the SNMP Agent as additional features.